2015
DOI: 10.1111/1460-6984.12140
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of parent‐implemented early‐literacy intervention for Spanish‐speaking children with language impairment

Abstract: The results presented here may stimulate future research on the print knowledge of Spanish-speaking children with LI. Sources of individual differences are important to determine. Caregivers may use the intervention presented here as a potential avenue for improving children's print knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 21 publications
(33 reference statements)
1
24
0
5
Order By: Relevance
“…Group differences in the total number of words between the treatment and control groups were reported. Pratt et al (2015) None reported. Faulkus et al (2016) reported that significant change occurred in the parent rating scale, which is a scale used by parents to rate their performance.…”
Section: Wake Et Al (2011)mentioning
confidence: 95%
See 2 more Smart Citations
“…Group differences in the total number of words between the treatment and control groups were reported. Pratt et al (2015) None reported. Faulkus et al (2016) reported that significant change occurred in the parent rating scale, which is a scale used by parents to rate their performance.…”
Section: Wake Et Al (2011)mentioning
confidence: 95%
“…Three studies did not include control groups (See Table 2). Four studies used a pre-post-test design with random assignment to a treatment or non-treatment control group (Allen and Marshall 2011;Girolametto et al 1996;Pratt et al 2015;Roberts and Kaiser 2012). One study used a cluster randomized trial (Wake et al 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a recent study conducted with upper‐middle‐class Spanish‐speaking participants has shown that parents successfully completed an 8‐week SBR intervention to improve early literacy skills of their preschool children with language disorder (Pratt et al . ). However, other studies have indicated no intervention effect for parental use of SBR strategies (Pile et al .…”
Section: Introductionmentioning
confidence: 97%
“…Studies focusing on 'dialogic reading' strategies (Whitehurst et al 1994) have shown that as a result of training, parents increased their use of wh-open-ended questions and expansions of children's utterances (Crain-Thoreson and Dale 1999, Dale et al 1996. Similarly, a recent study conducted with upper-middle-class Spanish-speaking participants has shown that parents successfully completed an 8-week SBR intervention to improve early literacy skills of their preschool children with language disorder (Pratt et al 2015). However, other studies have indicated no intervention effect for parental use of SBR strategies (Pile et al 2010) and parental difficulties in implementing SBR intervention with their children with DLD-mainly due to time constraints and difficulty with reading-and quite high attrition rates during intervention programmes (Justice et al 2011).…”
Section: Introductionmentioning
confidence: 99%